MAKNA MIKUL DUWUR MENDEM JERO DALAM NOVEL HATI SUHITA KARYA KHILMA ANIS - Fitriya Nur Kumala; Titik Indarti; Resdianto Permata Raharjo (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
This research aims to find out the meaning of Mikul Duwur Mendem Jero in the life of the novel Hati Suhita by Khilma Anis, help readers understand the meaning of Mikul Duwur Mendem Jero more deeply, and add broader insight. This meaning is found in the life of the main female character, Alina Suhita. Mikul Duwur Mendem Jero has the meaning of upholding the dignity, dignity, and honor of a woman in covering up the situation at hand. The principle of Mikul Duwur Mendem Jero is a message mandated by his grandfather that must be kept obedient, just like the Javanese women of ancient times. In this study the authors found some data that showed about the meaning of Mikul Duwur Mendem Jero. The female lead character who uses the principle of Mikul Duwur Mendem Jero describes that women have an honor that should be valued as the status of a wife. In the perspective, women have the idea that women are considered inferior to men. The position of a woman now has gender equality that balances the status of a man and a woman. However, a woman must also remember the obligations of a wife. The method used by the author is a qualitative research method, which is poured through a qualitative approach with descriptive results. The process carried out 1) Making observations, 2) Recording the results of observations, 3) Stringing with a structured arrangement, 4) Making conclusions. The materials used use reliable and accurate sources. Keywords: novel, mikul duwur, mendem jeru